The Threat from European Missile Defence System to Russian National Security - A. I. Podberezkin; J. Y. Parshkova (Vestnik MGIMO-Universiteta)
The article analyses the political and military aspects of progress in the dialogue between Russia and the U.S./NATO on cooperation in missile defense; investigates the past experiences and current state of cooperation between Russia and the Alliance on missile defense issues; examines the technical features of American missile defence systems today; finds a solution to question whether or not the European Missile Defence Program actually threatens Russia's nuclear deterrent and strategic stability in general; identifies both potential benefits and possible losses for Russia stemming from the development of cooperation with the United States and NATO in countering ballistic missile threats, or from refusal to have such cooperation. Evidently, the initiative of creation of a missile defense in Europe surely belongs to the USA. Washington has enormous technological, financial, economic, military and institutional capabilities in the field of a missile defense, exceeding by far other NATO member-states. In February 2010, the President of the United States B. Obama adopted a project "European Phased Adaptive Approach" (EPAA) as an alternative to G. Bush's global strategic missile defense plan. The first two stages of the Phased Adaptive Approach are focused on creating a system capable of intercepting small, medium and intermediate-range ballistic missiles. The possibility of intercepting long-range missiles is postponed to the third (2018) and forth phases (2020). Moscow finds especially troublesome the third and the fourth phases of Washington's project of creating a European segment of the global antiballistic missile system, considering prospective capabilities of the U.S. interceptor missiles 61 and the envisioned areas of their deployment. The U.S. counter-evidence is that phase four interceptors do not exist yet. Russia insists on getting the political and legal guarantees from the U.S. and NATO that their missile defense systems will not slash the efficiency of Russian nuclear deterrence forces.